Pengaruh Stres Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pt. Rhenus Logistics Indonesia Jakarta - Akbar, Muhammad; Husein, Aldino Muhamad (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to examine the effect of work stress and job satisfaction on the performance of PT. Rhenus Logistics Indonesia Jakarta employees. The independent variables in this study are work stress (X1) and job satisfaction (X2) with employee performance (Y) as the dependent variable. This study used a quantitative approach by obtained data through the distribution of questionnaires. The research participants were 52 people who working at PT. Rhenus Logistics Indonesia Jakarta. The results of this study prove that work stress has a negative and significant effect on employee performance. Job satisfaction variable has a positive and significant effect on employee performance. And the variables of work stress and job satisfaction have a significant effect simultaneously on employee performance.